A comprehensive review on biomass-derived producer gas as an alternative fuel: a waste biomass-to-energy perspective - Sharma, Prabhakar; Sharma, Avdhesh Kr.; Agbulut, Uemit (SPRINGER, 2025)
With the depletion of fossil fuel reserves and the worsening state of the environment, it is imperative to shift toward sustainable energy sources, with a special emphasis on biomass. The utilization of agricultural and forest waste biomass is a sustainable solution within the realm of green energy sources. This review provides a comprehensive analysis of pertinent research and explores the technical viability of substituting traditional energy sources with biomass. The producer gas (PG) is utilized in gas-fumigated dual-fuel engines and is suitable for application in off-grid and rural areas at lower power capacities. The adaptability of the dual-fuel strategy allows for seamless operation in PG-diesel mode without modifications, thus making it suitable for decentralized power generation in rural and urban areas, with notable environmental benefits. Substituting diesel with a PG-diesel combination leads to a notable reduction in NOx emissions and a minor decrease in particulate matter emissions. The lower calorific value of PG and the longer ignition delay contribute to minor power losses and reduced brake thermal efficiency. Moreover, the use of organic waste materials not only diminishes the amount of garbage sent to landfills but also decreases the release of greenhouse gases. This practice supports a circular economy by converting waste biomass to producer gas.
Keywords: Waste biomass-to-energy; Alternative fuel; Gasifier-engine system; Dual-fuel engine; Producer gas; BUBBLING FLUIDIZED-BED; DUAL-FUEL; DIESEL-ENGINE; CI ENGINE; EMISSION CHARACTERISTICS; PERFORMANCE EVALUATION; COMBUSTION PARAMETERS; NATURAL-GAS; GASIFICATION; BIODIESEL; Thermodynamics; Chemistry